La reciprocidad en la resolución de conflictos en el Vallespir (Rossellón, Francia): los delitos por ofensas sexuales - Gómez Mestres, Sílvia (ENDOXA, 2002)
This essay deals with norms and standards of behaviour which influencedat the early ninetheenth century the criminalization and then the resolution of verbal injuries andacts of violence at the Vallespir's French villages. The analysis of the judicial procedure including the system of its resolution and the final sentence, leads to taking legal norms and social perceptions into account as a sources of the law. The delictual obligation —who entails both a material and a moral amends— take spart on the relationship which links the guilty (debtor) to the victim (creditor). This study aims to study the altemative modes of resolution —such as transactions— and the kind ofreality affected byj uridical arrangements. The following questions are considered: A) In what extent the cost of a transaction depends on other transactions (e.g. the importance of a process of abstraction as a equivalent measures that is built by material and mental arrangements?) B) In what extent this cost depends on the singular conditions of the transaction (i.e. the circumstances under which the offence takes place and the transaction take spart, the quality of the protagonists and the global context)? C) It is possible to isolate, within the indemnity, the physical or moral amends —i.e. the pain—from the legal damages amends? D) Can we isole the hurt from their cost?